On the Use of F-transform on the Reduction of Concept Lattices - Madrid-Labrador, Nicolás Miguel; Hodakova, Petra (My University, 2015)
In this paper, we show that F-transform can be used to re- duce relational databases. Subsequently, we show that the respective concept lattice is reduced significantly as well. Moreover, we present a clarifying example of the procedure.
Keywords: Sistemas difusos; Lógica difusa; F-transform; Fuzzy Sets; Fuzzy Concept Analysis; Knowledge Reduction